ANALISIS STRATEGI PEMASARAN PADA SINAR JAYA KONVEKSI KUDUS UNTUK MENINGKATKAN DAYA SAING PERUSAHAAN MANUFAKTUR - Fathoni, Muhammad Yazid (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
Marketing strategy can be formulated by outlining the expectations of a company with the aim of getting more income opportunities than competitors of other companies. This study attempts to examine the marketing strategy implemented by the Sinar Jaya Konveksi Kudus manufacturing company based on a situation analysis by looking at market segmentation, target market, market position, and market mix. The method used in this study is a qualitative descriptive method. The source of the data in this study came from the Sinar Jaya Convection covection company. Data collection techniques in this study are by observation, interviews, and documentation. The findings revealed an increase in sales data from the last 3 years, namely 2018 to 2020, which experienced a significant increase in growth. In 2018 to 2019, the growth rate touched 11.7%, while in 2019 to 2020 the growth rate touched 16.5%. This increase can occur due to the precise and disciplined application of marketing strategy and market mix by the manufacturing company Sinar Jaya Convection.